Penyebaran Radikalisme di Media Penyiaran TV Indonesia - Ah. Fajruddin Fatwa (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This article focused on assessing the role of media broadcasting in the spreading religious radicalism in Indonesia. The emergence of numbers broadcasting and diversity of content used was not only have positive impact on the delivery of information in the community but also possible negative impact among the communities. The research found three identified negative impacts among society. First, spreading hatred information towards certain social or religious groups. Second, the potential for disintegration of national disintegration with messages that conflict with national values. Third, the potential for legal violations that occur due to the weak supervision of digital-based broadcast content. The research also found three weaknesses to develop the capacity Indonesia Broadcast committee first, restoring the weak of statement regulation and contradictory norm within the Broadcasting Behavior Guidelines and broadcasting behavior standard. Second, Developing the institutional coordination among the state institution, and strengthening the socialization of new Broadcasting Behavior Guidelines and broadcasting behavior standard.